PENGARUH PAJAK DAN DAN INFLASI TERHADAP PENDAPATAN NASIONAL: BUKTI EMPIRIS TAHUN 2014 – 2024 - Vivi Adeyani Tandean (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
This study aims to determine the effect of tax and inflation on national income. This type of research is quantitative research. Data were obtained from the Central Statistics Agency (BPS) and Bank Indonesia, then processed using IBM SPSS Statistics 22 for Windows. This research using data multiple regression analysis. The results of this research show tax has an effect on national income and inflation no has an effect on national income. This study proves that taxation still has a significant influence on the government's efforts to increase national income and provides empirical evidence for the government to formulate effective taxation policies to strengthen the country's fiscal position.